From team spirit to jealousy: the pitfalls of too much transparency - Alexander K. Koch; Albrecht Morgenstern (Institute for the Study of Labor (IZA), 2005)
Free riding in team production arises because individual effort is not perfectly observable. It seems natural to suppose that greater transparency would enhance incentives. Therefore, it is puzzling that team production often lacks transparency about individual contributions despite negligible costs for providing such information. We offer a rationale for this by demonstrating that transparency can actually hurt incentives. In the presence of career concerns information on the quality of task execution improves incentives while sustaining a cooperative team spirit. In contrast, making the identity of individual contributors observable induces sabotage behavior that looks like jealousy but arises purely from signal jamming by less successful team members. Our results rationalize the conspicuous lack of transparency in team settings with strong career concerns (e.g., co-authorship, architecture, and patent applications) and contribute to explaining the popularity of group incentive schemes in firms.
Keywords: D82; J30; L14; 330; teams; reputation; transparency; group incentives; sabotage